Avaliação de diferentes espaçamentos, altura e épocas de poda na cultura do pinhão manso na região de Selvíria-MS - Camargo, Francine Petenó de [UNESP] (2013)
The commercial interest in Brazil for the culture of jatropha, was awakened by presenting desirable characteristics, like the renewal of the national energy base as in family farming, favoring the man’s permanence on the field, because it is a culture with ample agricultural potential, distinguished by high productivity and satisfactory quality of oil for biodiesel production. The study evaluates the production of jatropha systems in different spacements, height and pruning time, becoming this research able to transform into parameters for recommendation cultural practices. The experiment was conducted in FEPE – Ilha Solteira Campus, located in Selvíria – MS, installed on 09/02/2010. The experimental design was the randomized blocks, in subdivided plots, with spacement in plots, and the height pruning factor and subplots. The spacements evaluated were 2x2 m, 3x2m , 3x3m , 4x2m and 4x3m, the pruning times were: 10 and 20 months after planting the seedlings and the following heights pruning: without pruning, 40 or 80 cm from ground, totaling 30 treatments with 3 reaplications. To follow the development of plants, seven evaluations were performed after planting, they were measured at plant height; stalk diameter; number of main branches and crop productivity. To the stalk diameter and plant height, we have the better spacement of plants’ growth: it was 3x3m. The different spacements did not influence significantly the production of the first year of culture, without pruning treatments were significantly more productive than the pruned. In the second year of jatropha production, we have in the spacements of 2x2m, 3x3m and 4x3m occurred a greater productivity in the treatments without pruning, becoming the more productive spacement the 4x3m with 266.67 kg ha-1